Escultura bidimensional del icono de Ernesto Guevara El Che en el auditorio exterior del nuevo edifico de la Universidad Técnica de Machala, fundamentado en la Técnica de la Escultura en chatarra - Luna Lanchi, Verónica Elizabeth (2012)
The work of the proposed research was based on the literature and field investigation that allowed us to establish the testing of hypotheses, the formulation of conclusions, recommendations and from these criteria the formulation of the proposal that allows us to formulate the Technical University Machala and therefore the cultural development of the province.